2012
DOI: 10.1002/jat.2754
|View full text |Cite
|
Sign up to set email alerts
|

Further experience with the local lymph node assay using standard radioactive and nonradioactive cell count measurements

Abstract: In a previous study, the predictive capacity of a modified local lymph node assay (LLNA) based on cell counts, the LNCC, was demonstrated to be closely similar to that of the original assay. In addition, a range of substances, including some technical/commercial materials and a range of agrochemical formulations (n = 180) have also been assessed in both methods in parallel. The results in the LNCC and LLNA were generally consistent, with 86% yielding an identical classification outcome. Discordant results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Results of the LLNA studies reported here have been published previously in Ball et al (2011) (surfactants), Basketter et al (2012) and Kolle et al (2012Kolle et al ( , 2013) (LLNA PS) without in-depth discussion of immunophenotyping (see Table 1). All studies were conducted prior to the animal testing ban implemented by the EU Cosmetics Directive/Cosmetics Regulation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Results of the LLNA studies reported here have been published previously in Ball et al (2011) (surfactants), Basketter et al (2012) and Kolle et al (2012Kolle et al ( , 2013) (LLNA PS) without in-depth discussion of immunophenotyping (see Table 1). All studies were conducted prior to the animal testing ban implemented by the EU Cosmetics Directive/Cosmetics Regulation.…”
Section: Resultsmentioning
confidence: 98%
“…() and Kolle et al . (, ) (LLNA PS) without in‐depth discussion of immunophenotyping (see Table ). All studies were conducted prior to the animal testing ban implemented by the EU Cosmetics Directive/Cosmetics Regulation.…”
Section: Resultsmentioning
confidence: 99%